Non-invasive neurostimulation techniques for the treatment of stimulant use disorders - Hendy, Jordan; Bereznicki, Hannah; Lundin, Robert M. (Frontiers in Psychiatry, 2026)
Addictive disorders remain important contributors to the overall burden of disease, and although many have established treatments, stimulant use disorders (StUDs) still lack effective management options. Neurostimulation techniques, such as Transcranial Magnetic Stimulation and Transcranial Direct Current Stimulation, have attracted addiction medicine researchers and clinicians, with many studies showing promise in reducing cravings and improving other clinical outcomes in participants, as well as modulating relevant brain areas. As a result, research output in this area is increasing rapidly. This narrative review aims to assess currently available research data on non-invasive neurostimulation techniques in patients with StUDs to inform future research requirements and clinical applications. This review was conducted using a comprehensive search strategy across PubMed, OVID Medline and PsycINFO databases, using terms including “stimulant use disorder*”, “transcranial magnetic stimulation” and “craving*”. The initial search was intentionally broad to effectively assess the breadth of literature on neurostimulation in addiction disorders generally, resulting in the return of 1317 sources. Search results were uploaded to Covidence and screened for inclusion. Upon narrowing the scope to isolate StUDs, 179 sources were included for full-text review, with 90 included for extraction. The most common outcome measure assessed was craving, with cognition, affective symptoms, sleep, and use patterns other frequently assessed measures. Overall, the results appear promising, with non-invasive neurostimulation variably improving cravings, cognition and affective outcomes in patients with StUDs. However, this review identified some limitations that require further research attention, including small sample sizes, short follow-up periods, protocol heterogeneity, and ill-representative samples.